2014
DOI: 10.3892/etm.2014.1856
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nerve growth factor in the prostate of male rats in response to chronic stress and sympathetic denervation

Abstract: Nerve growth factor (NGF) has been found in the normal prostate of the Wistar rat and is regarded as an important prostatic mitogen. We have previously shown that chronic stress induced epithelial hyperplasia while sympathetic denervation caused atrophy in the male Wistar rat prostate. NGF may have been a contributing mechanism to the hyperplasia and atrophy response that was observed. The aim of the present study was to investigate the expression of NGF in the prostate of the male rat in response to chronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…At the same time, the widespread distribution of NGF and its mRNA confirms that the prostate of rabbits is the main source of this neurotrophin for the seminal plasma, as already demonstrated in several other species, including humans (Arrighi et al 2010). A specific mitogenic action of NGF has also been reported in the prostate of rats (Huang et al 2014). Thus, our findings indirectly support results from recent experiments using seminal plasma of different species and indicate that the ovulation-inducing factor NGF is much more abundant in rabbits than in bulls, horses and pigs.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…At the same time, the widespread distribution of NGF and its mRNA confirms that the prostate of rabbits is the main source of this neurotrophin for the seminal plasma, as already demonstrated in several other species, including humans (Arrighi et al 2010). A specific mitogenic action of NGF has also been reported in the prostate of rats (Huang et al 2014). Thus, our findings indirectly support results from recent experiments using seminal plasma of different species and indicate that the ovulation-inducing factor NGF is much more abundant in rabbits than in bulls, horses and pigs.…”
Section: Discussionsupporting
confidence: 71%
“…A specific mitogenic action of NGF has also been reported in the prostate of rats (Huang et al. ). Thus, our findings indirectly support results from recent experiments using seminal plasma of different species and indicate that the ovulation‐inducing factor NGF is much more abundant in rabbits than in bulls, horses and pigs.…”
Section: Discussionmentioning
confidence: 83%
“…Sympathetic hyper-innervation also charges for the pathogenesis of BPH, which could result in ventral prostate hyperplasia (22). Moreover, nerve growth factor is involved in the pathogenesis of BPH in response to sympathetic hyper-innervation (23). In our study, not only storage LUTS but also voiding LUTS was significantly related with sodium intake.…”
Section: Discussionsupporting
confidence: 48%
“…Our results demonstrate that restraint stress (both acute and chronic) is sufficient to alter the expression of genes associated with tumor proliferation and metastasis in the rat prostate. Previous studies using a rat model of chronic stress (by restraint water immersion) have shown that 14 days of stress can induce histological changes in the prostate, as well as proliferation of epithelial cells of the ventral lobe of the prostate [ 53 , 54 ]. Although the expression of proliferation-associated genes was not measured in these studies, our data supports the notion that restraint stress can induce aberrant gene expression, which could potentially lead to increased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%